2016
DOI: 10.4028/www.scientific.net/msf.858.659
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Irradiation on 4H-SiC MOS Capacitors Processed under Different Annealing Conditions

Abstract: The overall radiation response to X-ray exposure of metal-oxide-semiconductor (MOS) capacitors, subjected to two different post-deposition-annealing (PDA) processes in N2O or POCl3 atmospheres, was investigated by capacitance-voltage (C-V) analyses. The production rate and saturation density of electrically active defects, different for the two oxides, demonstrated an additional contribution to the defects formation coming from the annealing treatements. The higher susceptibility of the POCl3-annealed oxide re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The commonly used gate material, SiO 2 , is inadequate for space MOS device application due to its low dielectric constant (∼3.9), high interface states (∼10 13 cm −2 •eV) [4], etc. Additionally, it has been found that commonly used annealing atmospheres for SiO 2 /SiC introduce additional defects under irradiation [5]. As an alternative, materials with larger permittivity, such as AlN, have been proposed to replace SiO 2 as the gate dielectric on 4H-SiC.…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used gate material, SiO 2 , is inadequate for space MOS device application due to its low dielectric constant (∼3.9), high interface states (∼10 13 cm −2 •eV) [4], etc. Additionally, it has been found that commonly used annealing atmospheres for SiO 2 /SiC introduce additional defects under irradiation [5]. As an alternative, materials with larger permittivity, such as AlN, have been proposed to replace SiO 2 as the gate dielectric on 4H-SiC.…”
Section: Introductionmentioning
confidence: 99%
“…13) In early studies on 4H-SiC MOS devices, the passivation techniques with N 2 O-and POCl 3 -annealing led to a different radiation susceptibility from that of thermal SiO 2 . [15][16][17] However, the radiation response after the passivation with B and Ba has not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%